Tailored pore-confined single-site iron(III) catalyst for selective CH4 oxidation to CH3OH or CH3CO2H using O2 - Manav Chauhan; Bharti Rana; Poorvi Gupta; Rahul Kalita; Chhaya Thadhani; Kuntal Manna (Nature Communications)
Abstract Direct oxidation of methane to valuable oxygenates like alcohols and acetic acid under mild conditions poses a significant challenge due to high C‒H bond dissociation energy, facile overoxidation to CO and CO2 and the intricacy of C−H activation/C−C coupling. In this work, we develop a multifunctional iron(III) dihydroxyl catalytic species immobilized within a metal-organic framework (MOF) for selective methane oxidation into methanol or acetic acid at different reaction conditions using O2. The active-site isolation of monomeric FeIII(OH)2 species at the MOF nodes, their confinement within the porous framework, and their electron-deficient nature facilitate chemoselective C‒H oxidation, yielding methanol or acetic acid with high productivities of $$38,592\,\upmu {{{\rm{mol}}}}_{{{{\rm{CH}}}}_{3}{{\rm{OH}}}}{{{{\rm{g}}}}_{{{\rm{Fe}}}}}^{-1}{{{\rm{h}}}}^{-1}$$ 38 , 592 μ mol CH 3 OH g Fe − 1 h − 1 and $$81,043\,\upmu {{{\rm{mol}}}}_{{{{\rm{CH}}}}_{3}{{{\rm{CO}}}}_{2}{{\rm{H}}}}{{{{\rm{g}}}}_{{{\rm{Fe}}}}}^{-1}{{{\rm{h}}}}^{-1}$$ 81 , 043 μ mol CH 3 CO 2 H g Fe − 1 h − 1 , respectively. Experiments and theoretical calculations suggest that methanol formation occurs via a FeIII-FeI-FeIII catalytic cycle, whereas CH3CO2H is produced via hydrocarboxylation of in-situ generated CH3OH with CO2 and H2, and direct CH4 carboxylation with CO2.